Biomedical Imaging - Mao, Youxin (IntechOpen, 2010)
Biomedical imaging is becoming an indispensable branch within bioengineering. This research field has recently expanded due to the requirement of high-level medical diagnostics and rapid development of interdisciplinary modern technologies. This book is designed to present the most recent advances in instrumentation, methods, and image processing as well as clinical applications in important areas of biomedical imaging. It provides broad coverage of the field of biomedical imaging, with particular attention to an engineering viewpoint. The goal of the book is to provide a wide-ranging forum in the biomedical imaging field that integrates interdisciplinary research and development of interest to scientists, engineers, teachers, students, and clinical providers.